Nadroparin Sodium Activates Nrf2/HO-1 Pathway in Acetic Acid-Induced Colitis in Rats - Yalniz, Mehmet; Demirel, Ulvi; Orhan, Cemal; Bahcecioglu, Ibrahim Halil; Ozercan, Ibrahim Hanefi; Aygun, Cem; Şahin, Kazım (Springer/Plenum Publishers, 2012)
Effects of nadroparin sodium, a low molecular weight heparin, in colitis was investigated by analyzing proteins implicated in nuclear factor E2-related factor-2/heme oxygenase-1 (Nrf2/HO-1) and nuclear factor kappa B (NF-kappa B) pathways. Twenty-eight rats were used. Colitis was induced by acetic acid (AA). Nadroparin sodium was given to prevention and treatment groups in addition to AA. Colitis was assessed histologically and levels of proteins were analyzed with Western blot. Nadroparin not only prevented and ameliorated the AA-induced colitis histopathologically but also decreased expression of colon NF-kappa B, activator protein-1, cyclooxygenase-2, tumor necrosis factor-alpha, and IL-6, which were significantly increased in group AA compared to control. The accumulation of Nrf2 in nuclear fraction and HO-1 found low in group AA was increased with nadroparin (p < 0.05). The mean malondialdehyde level increased with AA and was decreased significantly with nadroparin prevention and treatment (p < 0.001). Nadroparin sodium has both protective and therapeutic effects against colonic inflammation via exerting anti-oxidative and anti-inflammatory effects by modulating Nrf2/HO-1 and NF-kappa B pathways.
Keywords: nadroparin sodium; acetic acid-induced colitis; Nrf2/HO-1 pathway; COX-2